2014
DOI: 10.1016/j.jaci.2014.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy induces IgG antibodies that act through FcγRIIb to suppress IgE-mediated hypersensitivity

Abstract: Background Food anaphylaxis is triggered by specific IgE antibodies. Paradoxically, some individuals with significant IgE levels can ingest allergenic foods without incident. Similarly, subjects completing oral immunotherapy (OIT) tolerate food challenges despite persistent high-titer food-specific IgE. Objective To test whether IgG antibodies induced by food immunotherapy prevent food-induced anaphylaxis, and whether this occurs via the inhibitory receptor FcγRIIb. Methods Food allergy-susceptible Il4raF7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 42 publications
(44 reference statements)
6
147
1
Order By: Relevance
“…that had been found to not be sensitized to food ( Figure 2C). The appearance of lysosomal-associated membrane protein 1 (LAMP-1) at the cell surface of mast cells is an established surrogate marker for antigen/IgE-mediated histamine release (28,29), and we found that WT mast cells loaded with serum from food-sensitized Was -/-mice degranulated in response to stimulation with an antigen extract from conventional chow, but not in response to an extract from a protein-free, amino acid-based elemental diet ( Figure 2C). In contrast, mast cells loaded with serum from nonfood-sensitized animals were not activated by either food extract, which further demonstrated that IgE-dependent degranulation was antigen specific and established that screening of antibody IgG1 was observed (Supplemental Figure 1D).…”
Section: Sensitization To Food Antigens and Food Allergy Are Enrichedmentioning
confidence: 99%
“…that had been found to not be sensitized to food ( Figure 2C). The appearance of lysosomal-associated membrane protein 1 (LAMP-1) at the cell surface of mast cells is an established surrogate marker for antigen/IgE-mediated histamine release (28,29), and we found that WT mast cells loaded with serum from food-sensitized Was -/-mice degranulated in response to stimulation with an antigen extract from conventional chow, but not in response to an extract from a protein-free, amino acid-based elemental diet ( Figure 2C). In contrast, mast cells loaded with serum from nonfood-sensitized animals were not activated by either food extract, which further demonstrated that IgE-dependent degranulation was antigen specific and established that screening of antibody IgG1 was observed (Supplemental Figure 1D).…”
Section: Sensitization To Food Antigens and Food Allergy Are Enrichedmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of research studies in OIT for food allergies, with 18 RCT and 3 controlled clinical trials, demonstrated that OIT can achieve desensitization to a range of foods with some evidence for immunomodulatory changes, including a decrease in skin prick test response to the relevant food allergen and an increase in allergen-specific IgG 4 [95]. Experimental evidence has demonstrated that IgG antibodies suppress IgE-mediated food hypersensitivity via the inhibitory receptor FcgRIIb [96].…”
Section: Current Research Into Novel Routes Of Administration Oralmentioning
confidence: 99%
“…Similarly, and importantly, pre-immunotherapy but not post-immunotherapy sera from peanut-allergic patients efficiently sensitized normal basophils for peanut-induced activation, and IgG antibodies in post-immunotherapy serum inhibited the activation of basophils sensitized by pre-immunotherapy serum. This inhibition was blocked by anti-FcgRIIB antibodies [48 ]. Inhibition of IgE-dependent mast cell and basophil activation by food-specific IgG antibodies induced by oral immunotherapy may thus contribute to the beneficial effects of this treatment.…”
Section: Antibodies Modulate Quantitatively the Activation Of Mast Cementioning
confidence: 95%